Salt Stress Tolerance of Dark Septate Endophytes Is Independent of Melanin Accumulation - Gaber, Dalia A.; Berthelot, Charlotte; Camehl, Iris; Kovács, Gábor M.; Blaudez, Damien; Franken, Philipp (Frontiers in Microbiology, 2020)
Dark Septate Endophytes (DSEs) represent a diverse group of root-endophytic fungi that have been isolated from plant roots in many different natural and anthropogenic ecosystems. Melanin is widespread in eukaryotic organisms and possesses various functions such as protecting human skin from UV radiation, affecting the virulence of pathogens, and playing a role in development and physiology of insects. Melanin is a distinctive feature of the cell walls of DSEs and has been thought to protect these fungi from abiotic stress. Melanin in DSEs is assumed to be synthesized via the 1,8-dihydroxynaphthaline (DHN) pathway. Its function in alleviation of salt stress is not yet known. The aims of this study were: i. investigating the growth responses of three DSEs (Periconia macrospinosa, Cadophora sp. and Leptodontidium sp.) to salt stress, ii. analyzing melanin production under salt stress and, iii. testing the role of melanin in salt stress tolerance of DSEs. The study shows that the three DSE species can tolerate high salt concentrations. Melanin content increased in the hyphae of all DSEs at 100 mM salt, but decreased at 500 mM. This was not reflected in the RNA accumulation of the gene encoding scytalone dehydratase which is involved in melanin biosynthesis. The application of tricyclazole, a DHN-melanin biosynthesis inhibitor, did not affect either salt stress tolerance or the accumulation of sodium in the hyphae. In addition, melanin biosynthesis mutants of Leptodontidium sp. did not show decreased growth performance compared to the wild type, especially not at high salt concentrations. This indicates that DSEs can live under salt stress and withstand these conditions regardless of melanin accumulation.